Education quality of public and private universities in Bangladesh: Comparative perspective - Alam, Md. Nure; Ahmed, Tanjil (Journal of Educational Management and Instruction (JEMIN), 2024)
The quality of a nation's higher education system significantly influences its socioeconomic progress. Universities have immense capacity to promote economic well-being in underdeveloped nations. This study examines the relative quality of education at both private and public universities in Bangladesh. The study used a quantitative research method, with a total of 220 respondents participating in a cross-sectional survey. Data was collected physically via a face-to-face interview and online using a standardized Google form. The cross-sectional survey respondents found both offline and online methods convenient. Data were analyzed using Excel and SPSS. The study used statistical data to analyze crucial elements that influence the quality of education. Results reveal considerable disparities in educational quality evaluations between public and private universities. Both kinds of universities have reasonable teacher-student ratios, but private universities do better. 45% of public university respondents rate library facilities highly, compared to 22% at private universities. Research facilities prefer public universities, with 44% of respondents evaluating them highly, compared to just 14% for private universities. The quality of ICT facilities is seen as superior at private universities, with 57% of participants rating them highly, in contrast to a mere 11% in public universities. Private universities perceive international collaboration as more effective, with 67% of respondents rating it as high, compared to 38% in public universities. This investigation emphasizes the strengths and weaknesses of both public and private universities in Bangladesh, offering valuable insights for educational administrators and policymakers who are endeavoring to improve the quality of education in both sectors.